Association between egg intake and blood pressure in the USA: the INTERnational study on MAcro/micronutrients and blood Pressure (INTERMAP). Issue 18 (2nd December 2021) - Vu, Thanh-Huyen T; Van Horn, Linda; Daviglus, Martha L; Chan, Queenie; Dyer, Alan R; Zhong, Victor W; Gibson, Rachel; Elliott, Paul; Stamler, Jeremiah
Abstract: Objectives: To investigate associations of egg intake with blood pressure (BP) and the role of dietary variables and other macro- and micro-nutrients in the association. Design: We used cross-sectional data for the USA as part of the INTERnational study on MAcro/micronutrients and blood Pressure (INTERMAP). INTERMAP was surveyed between 1996 and 1999, including four 24-h dietary recalls, two 24-h urine collections and eight measurements of systolic BP and diastolic BP (SBP, DBP). Average egg intake (g/d) was calculated. Multivariable linear regression models were used to estimate the association between egg intake (per each 50 g/d or per quintile) and BP. The roles of dietary variables and other macro- and micro-nutrients in this association were also investigated. Setting: In the USA. Participants: In total, 2195 US INTERMAP men and women aged 40–59 years. Results: Participants were 50 % female, 54 % non-Hispanic White and 16 % non-Hispanic Black. Mean egg intake (sd ) in men and women was 30·4(29·8) and 21·6(20·5) g/d, respectively. Adjusting for demographics, socio-economics, lifestyle and urinary Na:K excretion ratios, we found non-linear associations with BP in non-obese women ( P -quadratic terms: 0·004 for SBP and 0·035 for DBP).The associations remained after adjusting for dietary variables, macro/micro nutrients or minerals. Dietary cholesterol was highly correlated with egg intake and may factor in the association. No association was found in obese women and in obese or non-obese men. Conclusion: Egg intake was non-linearly associated with SBP and DBP in non-obese women, but not in obese women or men. Underlying mechanisms require additional study regarding the role of obesity and sex.